Assessing News Literacy Skills between Journalism and Non-Journalism Students in Bangladesh - Begum, Monira; Khan, Abdur Razzaque (South Asian Journal of Social Sciences and Humanities, 2022)
During this Covid situation, the bulk numbers of students have confined themselves to new media more than ever, and their dependency level has already proved how severe this can be in the future. As a consequence of staying tangled with lots of confusing information, students often have to face dilemmas in news and sources. Judging this situation after conducting this study on Journalism and non-Journalism students, the finding uncovers a moderate knowledge level of students in identifying the news quality of a source of information. Normally, Journalism students are thought to be involved with formal media education; nevertheless, this study observes an expectant number of non-Journalism students are wrapping up themselves with media education with endeavors during this pandemic. What is more, this study follows W. J. Potter’s cognitive model of media literacy. With this model, this study digs the news literacy skills among students. In contrast, the study found moderate skills among students in cases of having more conscious mindful thought than automatic thought about the media messages, moderate motivation for news consumption, the satisfactory awareness level of media control and influence, and more trust in news media. But the shocking result is that all students have almost bottom-line knowledge about the media system, including knowledge of the media industry, media content, and media effects. So, all these knowledge gaps ultimately show the poor curriculums where enough practical-based media education is absent. Hence, this study proves the demand for more practical-based media education in all curriculums, especially at the tertiary levels universities in Bangladesh, with more importance.
Keywords: News literacy, media literacy, new media, media education, Journalism